Versatile Biomaterial Platform Enriched with Graphene Oxide and Carbon Nanotubes for Multiple Tissue Engineering Applications - Ignat, Simona-Rebeca (Int J Mol Sci, 2019)
Carbon-based nanomaterials, such as graphene oxide (GO) or carbon nanotubes (CNTs) are currently used in various medical applications due to their positive influence on biocompatibility, adhesion, proliferation, and differentiation, as well as their contribution to modulating cell behavior in response to nanomaterial substrates. In this context, in this study, novel flexible membranes based on cellulose acetate (CA) enriched with CNT and GO in different percentages were tested for their versatility to be used as substrates for soft or hard tissue engineering (TE), namely, for their ability to support human adipose-derived stem cells (hASCs) adhesion during adipogenic or osteogenic differentiation. For this purpose, differentiation markers were assessed both at gene and protein levels, while histological staining was performed to show the evolution of the processes in response to CA-CNT-GO substrates. Micro-CT analysis indicated porous morphologies with open and interconnected voids. A slightly lower total porosity was obtained for the samples filled with the highest amount of GO and CNTs, but thicker walls, larger and more uniform pores were obtained, providing beneficial effects on cell behavior and increased mechanical stability. The addition of 1 wt% GO and CNT to the biocomposites enhanced hASCs adhesion and cytoskeleton formation. The evolution of both adipogenic and osteogenic differentiation processes was found to be augmented proportionally to the GO-CNT concentration. In conclusion, CA-CNT-GO biomaterials displayed good properties and versatility as platforms for cell differentiation with potential as future implantable materials in TE applications.